Smooth Surfaces of Amalgam-Replacement-Materials: Finishing makes the difference. - Dr Alexander Behlau; Dr.rer.nat. Isabelle Behlau; Dr.techn. Thomas Schmid; Prof. Michael Payer; Dr.rer.nat Gerd Leitinger; Dr.med.dent. Katharina Hanscho; Dr.med.dent. Lumnije Kqiku-Biblekaj; Prof.Karl Glockner (Elsevier, 2023)
Aim or Purpose: Due to the need of the investigation of the longevity of amalgam-replacement materials since the Minamata Convention, the aim of the present study was to investigate the influence of different finishing methods for varying amalgam-replacement materials on surface roughness over time. Materials and Methods: In the present in-vitro study standardized metal printed molds were filled with the following glass-ionomer-cements: DeltaFil, Equia Forte HT, IonoStar Molar and Ketac Universal and the alkasite Cention Forte. Surface roughness (Sa) of the samples (n=300) was analysed with a noncontact profilometer (InfiniteFocus, Bruker Alicona) at three time points: (1) after finishing, (2) after 30 days and (3) after an aging simulation using thermocycling. Different finishing methods (n=10 per group) were compared: (A) without finishing (control group), (B) arkansas bur, (2) diamond bur, (3) tungsten carbide bur, (4) SofLex discs in descending grit size and (5) coarse SofLex discs in combination with a silicone polisher. Results: DeltaFil was the only filling material with a stable smooth surface over time. Conventional glass-ionomer-cements and hybrid glass-ionomer cements showed smoother surfaces than high-viscosity glass-ionomer-cements. While conventional glass-ionomer-cements had the smoothest surfaces using tungsten carbide bur, alkasite was smoothest using SofLex discs. Conclusions: Our results support the assumption that it makes a huge difference which finishing is used with which filling material, thus giving hints for practitioners.